1998
DOI: 10.1093/humrep/13.3.576
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in 447 couples undergoing intracytoplasmic sperm injection--prevalence, types, sex distribution and reproductive relevance

Abstract: Chromosomal abnormalities are thought to be a major contributor to the genetic risks of infertility treatment by intracytoplasmic sperm injection (ICSI). Apart from abnormalities arising de novo, abnormal karyotypes in pregnancies conceived through assisted reproductive technology may be directly derived from predisposing parental aberrations. In a prospective study we have analysed the chromosomes of 868 male and female patients prior to planned ICSI treatment. A total of 33 aberrant karyotypes was diagnosed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(46 citation statements)
references
References 44 publications
5
39
0
2
Order By: Relevance
“…Evaluation of 15 similar studies from the literature including a total of 9374 cases showed 6.54% chromosomal anomaly rate (Table 3) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In our study 11.74% of all cases revealed chromosomal alteration including inv (9).…”
Section: Discussionsupporting
confidence: 62%
“…Evaluation of 15 similar studies from the literature including a total of 9374 cases showed 6.54% chromosomal anomaly rate (Table 3) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In our study 11.74% of all cases revealed chromosomal alteration including inv (9).…”
Section: Discussionsupporting
confidence: 62%
“…Comparison of our results with the review of the literature shows a higher incidence (4-fold) of gonosomal, in particular, numerical gonosomal, chromosomal anomalies. In Table 2, in studies with a large sample size but low incidence of total chromosomal abnormality,[101218] patients are mostly oligospermic rather than azoospermic, but in surveys with small sample size[25] or a sample size similar to our study,[23] which showed high incidence of total chromosomal abnormality, cases are totally azoospermic or have the same number with oligospermia cases. On the other hand, Morel et al .,[16] in their study in the review of the literature, reported that frequency of KS in azoospermia (10.17) is about 19-fold more frequent than in oligospermia (0.57).…”
Section: Discussionsupporting
confidence: 47%
“…This study assessed the prevalence of chromosomal abnormalities in a large cohort of non-selected infertile couples attending an ART program, and the pregnancy outcome of couples with abnormal karyotype who successfully underwent to ICSI. The frequency of karyotype anomalies in infertile subject has been reported in several studies to range from 1.97% to 18.0% [1][2][3][4][5][6][7][8][9][10]. Differences in sample size, patient demographics and criteria for patient inclusion may help to explain, at least in part, the differing frequencies.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown a higher prevalence, in comparison to the general population, of chromosomal abnormalities in both men and women with fertility problems [1][2][3][4][5][6][7][8][9][10]. Carriers of chromosomal anomalies are at increased risk to produce genetically unbalanced gametes and consequently, in addition to reproductive impairment, to have an increased risk of adverse pregnancy outcomes such as miscarriage, still birth, and malformed offspring [11].…”
Section: Introductionmentioning
confidence: 99%